Ultra-wideband CMOS power amplifier for wireless body area network applications: a review - Nagham Gamal El-Feky; Mostafa Hassan Fedawy; Dina Mohamed Ellaithy (Institute of Advanced Engineering and Science, 2023)
A survey on ultra-wideband complementary metal-oxide semiconductor (CMOS) power amplifiers for wireless body area network (WBAN) applications is presented in this paper. Formidable growth in the CMOS integrated circuits technology enhances the development in biomedical manufacture. WBAN is a promising mechanism that collects essential data from wearable sensors connected to the network and transmitted it wirelessly to a central patient monitoring station. The ultra-wideband (UWB) technology exploits the frequency band from 3.1 to 10.6 GHz and provides no interference to other communication systems, low power consumption, low-radiated power, and high data rate. These features permit it to be compatible with medical applications. The demand target is to have one transceiver integrated circuit (IC) for WBAN applications, consequently, UWB is utilized to decrease the hardware complexity. The power amplifier (PA) is the common electronic device that employing in the UWB transmitter to boost the input power to the desired output power and then feed it to the antenna of the transmitter. The advance in the design and implementation of ultra-wideband CMOS power amplifiers enhances the performance of the UWB-transceivers for WBAN applications. A review of recently published CMOS PA designs is reported in this paper with comparison tables listing wideband power amplifiers' performance.